META II: Digital Vellum in the Digital Scriptorium. - LONG, DAVE (Communications of the ACM, 2015)
The article considers a paper written in 1962 by computer scientist Dewey Val Schorre that describes a computer compiler called META II. The author quotes various passages from the text that reference concepts including recursion, monadic composition, and the VALGOL computer programming language. He also describes how he replicated Val Schorre's work with the aid of the Python programming language and a process called bootstrapping. In his view META II can be characterized as a self-applicable compiler.